NOTES ON THE ASTERACEAE OF SUMATERA - SRI SUDARMIYATI TJITROSOEDIRDJO (SEAMEO BIOTROP, 2002)
An account of the tribe composition, endemic taxa, comparison with adjacent areas and weedy Asteraceae of Sumatera is given. Based on the records of January 2000, there are 133 species of 74 genera in 11 tribes.Â The tribe Heliantheae is the largest, with 28% of the total number of the genera, followed by Astereae with 15%, Inuleae 12%, Senecioneae 10%, Anthemideae, Eupatorieae and Lactuceae 8%, the other tribes are represented by 4% or less. The most diverse genus is Blumea with 14 species. Other genera are only represented by 10 species or less, usually 4, or 3, or 2, and mostly by 1 species only. Thirty nine or about 53% are exotic genera and the native ones are less than half of the total number of the genera. In terms of indigenous and endemic species, Sumatera is richer than Java. There are 1 genus, 7 species and 2 varieties of Asteraceae endemic to Sumatera. A number of 43 important weed species were introduced from Tropical America, Africa, Asia and Europe. Among these Chromolaena odorata and Mikania micrantha are reported as the most noxious ones.Â List of the genera and species recorded in Sumatera is provided in this paper. Key words : Asteraceae/Sumatera/compositions/endemic species/distribution/weedy Asteraceae